Hubungan Persepsi dengan Tingkat Kepuasan Masyarakat terhadap Program Mina Padi pada Lahan Suboptimal di Desa Sungai Rebo Kecamatan Banyuasin I Kabupaten Banyuasin - Arbi, Muhammad; Faradillah, Faradillah; Junaidi, Yulian (Seminar Nasional Lahan Suboptimal, 2023)
Arbi, M., Faradilla, F., & Yulian, J. (2023). The relationship between perceptions and the level of community satisfaction with the mina padi program on suboptimal land in Sungai Rebo Village, Banyuasin I District, Banyuasin Regency, South Sumatra Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 199-205).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Mina Padi Program is one of the programs in Sungai Rebo Village, Banyuasin Regency which aims to empower the community. The public can provide perceptions of the Mina Padi program through the characteristics of innovation contained in the program, namely based on the relative advantages that can be obtained, complexity, suitability to the local environment, as well as results and examples. This research aimed to measure the perception and level of community satisfaction with the Mina Padi Program and analyze the relationship between perception and the level of community satisfaction with the success of the Mina Padi Program in Sungai Rebo Village, Banyuasin Regency. This research used a survey method by conducting interviews and questionnaires with 30 members of the Bina Tani Berkah community group who received the benefits of the Mina Padi Program. The types of data used in this research were primary data and secondary data. The data processing method to answer the first objective used the Likert scale method, then to answer the second objective used the Spearman Rank correlation test. The research results showed the public's perception of the Mina Padi Program was relatively high. The level of community satisfaction with the Mina Padi Program in Sungai Rebo Village was satisfaction. Based on the results of Spearman's analysis, it was known that there is a significant relationship between perception and the level of community satisfaction with the Mina Padi Program with a correlation coefficient of 0.697 with a fairly strong relationship.